2019
DOI: 10.1002/jso.25610
|View full text |Cite
|
Sign up to set email alerts
|

The impact of postoperative morbidity on survival in patients with metastatic colon and rectal cancer

Abstract: Introduction: Avoiding postoperative morbidity is essential in patients with advanced cancer. To further improve treatment in stage IV colorectal cancer, knowledge about risk factors which effect short‐ and long‐term outcomes is important. Methods: All stage IV colon and rectal cancer who underwent elective surgery between 2004 and 2015 were included (n = 345). We compared resectable colon and rectal patients, and unresectable colon and rectal cancer patients. Results: Median follow‐up duration was 22.2 (unres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
(81 reference statements)
3
10
0
Order By: Relevance
“…In addition, our study (Supplementary Table S1) and previous studies have shown the negative impact of postoperative morbidity on long-term survival after hepatetcomy for CRLM. 34,35 Finally, the number of patients included in our study was too small to stratify outcomes according to all sites of extrahepatic recurrence. However, fusion of bicentric data and thorough evaluation of followup imaging by specialized radiologists in each center contributed to precise evaluation of intrahepatic and extrahepatic recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study (Supplementary Table S1) and previous studies have shown the negative impact of postoperative morbidity on long-term survival after hepatetcomy for CRLM. 34,35 Finally, the number of patients included in our study was too small to stratify outcomes according to all sites of extrahepatic recurrence. However, fusion of bicentric data and thorough evaluation of followup imaging by specialized radiologists in each center contributed to precise evaluation of intrahepatic and extrahepatic recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, MVC is performed in only 1.2-12% of patients with colon cancer. 14,15,21,22 In our study, MVC was performed in 44.8% of patients with LACC, which accounts for 19.2% of a total number of colon resections for cancer. Higher incidence of MVC in our series can be attributed to strict selection criteria in the aforementioned studies, as well as to a significantly higher proportion of late diagnosed patients in our population.…”
Section: Discussionmentioning
confidence: 84%
“…b OS for patients without primary tumor resection method, is preferentially recommended for mCRC patients by various guidelines [6,7], which were proved to be the protective factor in both PTR and non-PTR groups in our study. Although PTR may delay chemotherapy, which could decrease the latter's efficacy [13][14][15][16], PTR could also reduce tumor loading to improve response rates to chemotherapy [27]. Therefore, decision-making should balance the surgery-related benefits and risk.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of unresectable mCRC patients from 17 retrospective studies by Ha et al revealed significantly improved survival associated with PTR [ 28 ]. Despite the benefits of PTR, it may delay the time in the administration of chemotherapy and increases the potential risk of surgery-related complications, which may subsequently increase death risk [ 13 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation